Role of Gender Equity in Sustainable Development - Das, Supriya (Indian Journal of Hill Farming, 2018)
Equity is an essential building block in sustainable development of every sphere of society. Gender analysis is a tool to better understand the realities of the women and men, girls and boys whose lives are impacted by planned development activities. Sustainable development requires the full and equal participation of women at all levels alongside men. It is clearly inappropriate to try and address problems, to identify strategies, or to implement the programmes, if only half of the population (men/women) concerned is involved in the process. Partnerships and equality between men and women are the basis of strong families and viable societies in a rapidly changing world. Women have been consistently excluded from decision-making across history and societies; which resulted imbalance, marginalization, suffering and conflicts. Creating greater gender equity will contribute to building peaceful, democratic and prosperous societies. Even in sustainable development of agriculture, role of women is of paramount importance and there is urgent need to devise women specific technologies for better participation and involvement of women in decision making.